Pharmacokinetic evaluation of the interaction between oral kaempferol and ethanol in rats - Zhou Zhaoxiang; Wang Meng; Guo Zengjun; Zhang Xiaoying (Acta Pharmaceutica, 2016)
This study was aimed at investigating the effect of ethanol on oral bioavailability of kaempferol in rats, namely, at disclosing their possible interaction. Kaempferol (100 or 250 mg kg-1 bm) was administered to the rats by oral gavage with or without ethanol (600 mg kg-1 bm) co-administration. Intravenous administration (10 and 25 mg kg-1 bm) of kaempferol was used to determine the bioavailability. The concentration of kaempferol in plasma was estimated by ultra high performance liquid chromatography. During coadministration, a significant increase of the area under the plasma concentration-time curve as well as the peak concentration were observed, along with a dramatic decrease in total body clearance. Consequently, the bioavailability of kaempferol in oral control groups was 3.1 % (100 mg kg-1 bm) and 2.1 % (250 mg kg-1 bm). The first was increased by 4.3 % and the other by 2.8 % during ethanol co-administration. Increased permeability of cell membrane and ethanolkaempferol interactions on CYP450 enzymes may enhance the oral bioavailability of kaempferol in rats.